The RGD region of bone sialoprotein affects metabolic activity in mice - Nagasaki, Karin; Nagasaki, Atsuhiro; Taylor, Jocelyn M.; Kear, Bernice D.; Ma, Yinyan; Somerman, Martha J.; Gavrilova, Oksana (Frontiers in Dental Medicine, 2023)
Bone sialoprotein (BSP) is a key regulator of mineralized tissue formation. Previously, we generated BSP-KAE knock-in mice (KAEKI mice) by substituting a non-function KAE (lysine-alanine-glutamic acid) for the integrin-binding RGD (arginine-glycine-aspartic acid) sequence and reported a vital role of the BSP-RGD motif in modulating the periodontal ligament (PDL). Specifically, histologically a disorganization of the PDL was noted, resulting in a weakened function of the PDL as measured by dynamic mechanical analysis. Intriguingly, also noted was a weight gain as KAEKI mice aged. While several proteins associated with mineralized tissues are reported to affect energy metabolism, the metabolic role of the BSP-RGD region has yet to be elucidated. Here we focus on defining the role of the BSP-RGD region in metabolic activity. Body weight, body composition, and caloric intake were measured in wild type (WT) and KAEKI mice. Energy expenditure was estimated using energy balance technique. Epididymal fat, interscapular fat, and liver were harvested for histological analysis. Systemic metabolic phenotype was assessed by sera analyses, insulin tolerance and glucose tolerance tests. The results showed that KAEKI mice developed mild obesity starting from 13 weeks postnatal (wpn). The increase in body weight correlated with an increase in lean mass and visceral adiposity. Histological examination revealed adipocyte hypertrophy in white epididymal fat and interscapular brown fat in KAEKI vs. WT mice at 17 wpn. Metabolic profiling indicated that KAEKI mice had dyslipidemia and hyperleptinemia but no significant changes in glucose metabolism. Energy balance analyses revealed that hyperphagia preceded weight gain in KAEKI mice. These data suggest that the RGD-region of BSP affects energy metabolism by regulating food intake, with further studies warranted to uncover the underlying mechanisms.